Synthesis and Evaluation of a Library of Trifunctional Scaffold-Derived Compounds as Modulators of the Insulin Receptor - Fabre, Benjamin; Pícha, Jan; Vaněk, Václav; Selicharová, Irena; Chrudinová, Martina; Collinsová, Michaela; Žáková, Lenka; Buděšínský, Miloš; Jiráček, Jiří (ACS combinatorial science, 2016)
We designed a combinatorial library of trifunctional scaffold-derived compounds, which were derivatized with 30 different in-house-made azides. The compounds were proposed to mimic insulin receptor (IR)-binding epitopes in the insulin molecule and bind to and activate this receptor. This work has enabled us to test our synthetic and biological methodology and to prove its robustness and reliability for the solid-phase synthesis and testing of combinatorial libraries of the trifunctional scaffold-derived compounds. Our effort resulted in the discovery of two compounds, which were able to weakly induce the autophosphorylation of IR and weakly bind to this receptor at a 0.1 mM concentration. Despite these modest biological results, which well document the well-known difficulty in modulating protein-protein interactions, this study represents a unique example of targeting the IR with a set of nonpeptide compounds that were specifically designed and synthesized for this purpose. We believe that this work can open new perspectives for the development of next-generation insulin mimetics based on the scaffold structure.
Keywords: Reproducibility of Results; vazba proteinů; vysokoúčinná kapalinová chromatografie; Molecular Structure; Solid-Phase Synthesis Techniques; insulin mimetics; techniky kombinatorické chemie; Insulin; Receptor, Insulin; měď; library; Copper; Small Molecule Libraries; scaffold; molekulární struktura; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; insulin receptor; Azides; azidy; techniky syntézy na pevné fázi; protein-protein interactions; Combinatorial Chemistry Techniques; knihovny malých molekul; trifunctional; receptor inzulinu; inzulin; Protein Binding